Syndromic forms of congenital hyperinsulinism - Zenker, Martin; Mohnike, Klaus; Palm, Katja (Frontiers in Endocrinology, 2023)
Congenital hyperinsulinism (CHI), also called hyperinsulinemic hypoglycemia (HH), is a very heterogeneous condition and represents the most common cause of severe and persistent hypoglycemia in infancy and childhood. The majority of cases in which a genetic cause can be identified have monogenic defects affecting pancreatic β-cells and their glucose-sensing system that regulates insulin secretion. However, CHI/HH has also been observed in a variety of syndromic disorders. The major categories of syndromes that have been found to be associated with CHI include overgrowth syndromes (e.g. Beckwith-Wiedemann and Sotos syndromes), chromosomal and monogenic developmental syndromes with postnatal growth failure syndromes (e.g. Turner, Kabuki, and Costello syndromes), congenital disorders of glycosylation, and syndromic channelopathies (e.g. Timothy syndrome). This article reviews syndromic conditions that have been asserted by the literature to be associated with CHI. We assess the evidence of the association, as well as the prevalence of CHI, its possible pathophysiology and its natural course in the respective conditions. In many of the CHI-associated syndromic conditions, the mechanism of dysregulation of glucose-sensing and insulin secretion is not completely understood and not directly related to known CHI genes. Moreover, in most of those syndromes the association seems to be inconsistent and the metabolic disturbance is transient. However, since neonatal hypoglycemia is an early sign of possible compromise in the newborn, which requires immediate diagnostic efforts and intervention, this symptom may be the first to bring a patient to medical attention. As a consequence, HH in a newborn or infant with associated congenital anomalies or additional medical issues remains a differential diagnostic challenge and may require a broad genetic workup.